2022
DOI: 10.1002/adom.202200583
|View full text |Cite
|
Sign up to set email alerts
|

Localized Surface‐Plasmon Enhanced Near‐Infrared Organic Photodetector

Abstract: Near infrared (NIR) organic photodetector (OPD) has exhibited tremendous potential in research due to mechanical flexibility, optoelectronic tunability, and low cost. However, the limited NIR light absorption, low carrier mobility, and relatively low photon‐to‐electron conversion efficiency in organic photoactive layer have restricted further development of OPD. To address these challenges, localized surface‐plasmon resonance (LSPR) enhanced D18:Y6 OPD is systematically designed and fabricated with uniform Ag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The comparison of the performances of the previously reported NIR narrowband PDs is summarized in Table S3. However, the calculated D * value is overestimated because the calculation only accounts for shot noise while ignoring Johnson noise and flicker noise. , Therefore, noise spectral density as a function of frequency at a −0.1 V bias was analyzed, as shown in Figure S10. It is observed that the OPDs with AuNRs-CuSCN hybrid HTL produce much less noise than that of the control device, leading to a higher D * of 1.57 × 10 12 Jones as compared to that with CuSCN HTL (1.05 × 10 12 Jones).…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of the performances of the previously reported NIR narrowband PDs is summarized in Table S3. However, the calculated D * value is overestimated because the calculation only accounts for shot noise while ignoring Johnson noise and flicker noise. , Therefore, noise spectral density as a function of frequency at a −0.1 V bias was analyzed, as shown in Figure S10. It is observed that the OPDs with AuNRs-CuSCN hybrid HTL produce much less noise than that of the control device, leading to a higher D * of 1.57 × 10 12 Jones as compared to that with CuSCN HTL (1.05 × 10 12 Jones).…”
Section: Resultsmentioning
confidence: 99%
“…The large donor/acceptor interface and the percolating structure facilitate the photogenerated exciton dissociation and charge transport to solve the problems in organic systems including large exciton binding energy and short diffusion length for photogenerated charges, which dramatically improves the photo-to-electron conversion efficiency of the device. Meanwhile, ternary heterojunction active layers are also investigated mainly to extend the response spectrum of the device. , In addition, to boost the light–matter interaction, methods such as optical cavity resonance, localized surface plasmon, waveguide modes, and optical scattering from nanostructures are introduced to modulate the light distribution in the devices.…”
Section: Photodetector Materials and Structuresmentioning
confidence: 99%
“…Meanwhile, ternary heterojunction active layers are also investigated mainly to extend the response spectrum of the device. 78,79 In addition, to boost the light− matter interaction, methods such as optical cavity resonance, 80 localized surface plasmon, 81 waveguide modes, 82 and optical scattering from nanostructures 83 are introduced to modulate the light distribution in the devices.…”
Section: Photodetector Materials and Structuresmentioning
confidence: 99%
“…Localized surface plasmon resonance (LSPR) has been reported to be effective in enhancing the light-matter interactions by coupling and trapping freely propagating plane waves into an adjacent semiconductor. To date, researchers have discovered a series of optical antenna materials with pronounced plasmonic resonance effects, including Au [139], Ag [140], Al [141], Pt [142], Pd [143], etc. Therefore, integrating plasmonic optical antennas with 2DLMs can overcome the notorious disadvantage of insufficient light absorption.…”
Section: Light Harvesting Enhancementmentioning
confidence: 99%